Analisis Penerapan Income Audit Dalam Meningkatkan Akurasi Laporan Keuangan: Studi Kasus Hotel Kini Villa Sumbawa - Wijaya, Yuda Apriandi; Cahyaningtyas , Susi Retna; Kartikasari , Nungki (Jurnal Riset Mahasiswa Akuntansi, 2025)
Revenue is a critical component of financial reporting in hotels, particularly in small-scale hospitality businesses that are more vulnerable to recording errors and fraud. This study aims to analyze how the implementation of income audit can improve the accuracy of financial statements at Kini Villa Hotel Sumbawa. A descriptive qualitative approach was applied, with data collected through observation, in-depth interviews, and documentation. The findings indicate that prior to the implementation of income audit, various issues were identified such as duplicate transactions, recording omissions, and reconciliation discrepancies. After implementation, daily verifications, audits of discounts and refunds, and data reconciliations became more systematic and effective. Improved accuracy was also reflected in faster report preparation and enhanced financial transparency. The study concludes that income audit plays a vital role in strengthening internal control systems and enhancing the reliability of hotel financial information.